Gender Parity in Parliament: A Panacea for the Promotion and Protection of Women's Rights in Nigeria - Eniola, Bolanle Oluwakemi (Frontiers in Sociology, 2018)
Women's rights are part of the fundamental human rights that are recognized in international human rights treaties. While Nigeria has acceded to a number of international instruments on the promotion and protection of women's rights, women in this country have yet to realize their rights. The Nigerian Constitution requires that international treaties be domesticated before they apply in the country. Most of the international instruments on the promotion and protection of women's rights have not been domesticated. One of the reasons is inadequate representation of women in the country's parliament. This is despite the fact that the right of women to participate in decision making processes at all levels is guaranteed in both international and domestic instruments. This paper examines why Nigerian women are not adequately represented in parliament and the implications for the promotion and protection of their rights. It concludes that gender parity in the legislative houses is essential to agitate for and promote women's rights in this country.